Recognition Code of ZNF191(243-368) and Its Interaction with DNA - Dongxin Zhao; Zhongxian Huang (Bioinorganic Chemistry and Applications)
ZNF191(243-368) is the C-terminal region of ZNF191 which contains a putative DNA-binding domain of four Cys2His2 zinc finger motifs. In this study, an expression vector of a fusion protein of ZNF191(243-368) with glutathione-S-transferase (GST) was constructed and transformed into Escherichia coli BL21. The fusion protein GST-ZNF191(243-368) was expressed using this vector to investigate the protein-DNA binding reaction through an affinity selection strategy on the basis of the binding quality of the zinc finger domain. Results showed that ZNF191(243-368) can selectively bind with sequences and react with genes which contain an AGGG core. However, the recognition mechanism of Cys2His2 zinc finger proteins to DNA warrants further investigation.